The transitional experiences of an international student facing chronic physical illness - Matsagopane, Yaone Duduetsang (Journal of International Students, 2023)
This article illuminates the author’s transitional experiences during a chronic physical illness in China. Although many studies have considered patients’ chronic physical illnesses, few have considered international students’ experiences of chronic physical illness by means of the narrative approach. The author examines her chronic physical illness journey based on transitional experience and narrative identity theory. The narrative indicates a sense of identity, agency, and adaptation to change, and the exploration of such experiences could significantly contribute to the literature on students’ chronic physical health from a student’s perspective.